Factors affecting Canadian veterinarians’ use of analgesics when dehorning beef and dairy calves - Hewson, Caroline J. (Canadian Veterinary Medical Association, 2007)
Data collected through a national, randomized mail survey (response rate 50%) were used to identify reasons why veterinarians were likely (i) to use analgesic drugs when dehorning calves, and (ii) to perceive dehorning without analgesia as very painful. Logistic regression analysis indicated that veterinarians were more likely to be analgesic users the more they perceived that dehorning without analgesia was painful (OR = 1.7, P < 0.001). Other positive influences were if the veterinarian worked in British Columbia or Alberta (OR = 5.9, P = 0.005), and if they were primarily in dairy practice (OR = 3.7, P = 0.012) rather than beef practice. This effect of dairy practice was negated if the veterinarian also perceived that owners were unwilling to pay for analgesia (interaction term: OR = 0.25, P = 0.038). Veterinarians were also less likely to perceive dehorning without analgesia as very painful if they perceived that owners were unwilling to pay (OR = 0.58, P = 0.029). However, this effect on pain perception was offset by concern for personal safety (OR = 2.7, P = 0.015). The results are consistent with the relatively high level of outreach about animal welfare among farmers and veterinarians in the western provinces. The results confirm that many veterinarians’ approach to pain management for dehorning is influenced considerably by concern about cost. However, pain management for dehorning is not expensive and there is unequivocal evidence that dehorning calves without pain management causes significant distress. Continuing education of veterinarians should help to increase analgesic usage.